If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 4x = 23 Solving 2c + 4x = 23 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4x' to each side of the equation. 2c + 4x + -4x = 23 + -4x Combine like terms: 4x + -4x = 0 2c + 0 = 23 + -4x 2c = 23 + -4x Divide each side by '2'. c = 11.5 + -2x Simplifying c = 11.5 + -2x
| Y-3(-1)=4 | | Y-3(-2)=4 | | 3.0+3.0x=3.2 | | 4-x=[2-3x] | | 7-.625x=-2 | | .75x=180 | | 4(0)+2y=6 | | 100=10(logI-logI[0]) | | ax+by+1=0 | | 4(-1)+2y=6 | | 100=.50x-(15+.05x) | | 0.50x-(15+.05x)=100 | | (5x+1)(5x+1)=9 | | 2=6(5-4w) | | F-1(2)=2x-6 | | 8x+12y=144 | | 3(7a-1)= | | (3x-2)+(2x+4)+(x+10)=0 | | 8-2c=9 | | 52=-2w*3L | | 7-9g+8+2g= | | 10(-10x-5)= | | 10p+9-11-p=-4p+-8-6p-3 | | 7+9g-8+2g= | | 3x-(9)=75+x | | 3x-2+2x+4+x+10=o | | -61=12a-1 | | 3x^2+3y^2=6 | | 53=5-2u | | 1-8k-9k-4= | | 29-4x=4 | | 2y+9fory=-6 |